Exploring Employability, Program Relevance and Job Satisfaction among BS Criminology Graduates - Nayoyos-Refugia, Jennifer M. (Future Science / FSH-PH Publications, 2024)
Workplace fulfillment is critical for motivating workers, boosting productivity, and improving general wellbeing. It also emphasizes relevance of the program to match the industrial demands, as this drives the creation of educational policies, practices, funding allocation, and curriculum design to effectively meet the demands of the general public, employers, and students. This descriptive study investigated the employment status, program relevance, and job satisfaction of LSPU-SPCC BS Criminology graduates from batches 2015 to 2019. The study utilized a descriptive design with a mixed-methods approach having 205 graduates that responded the self-made questionnaire. Result shows that majority of graduates were found to be male and of single civil status, and they were mostly employed by governmental agencies with permanent status, particularly the Philippine National Police. The ratings for skills, curriculum, OJT programs, faculty competency and expertise, instruction and work-related values were favourable to their career but there are prospects for development. Graduates feel quite satisfied with their jobs, particularly with regard to the pay, perks, and job security, although there is space for improvement in terms of promotion chances. Job satisfaction was found to be influenced by healthy working relationships. Employers can take advantage of these findings to foster a positive work environment and provide opportunities for career growth, leading to increased job satisfaction and overall organizational success. The findings suggest that continuous program improvement, guided by program administrators and educators, is necessary to better prepare graduates for careers in criminology.